2019
DOI: 10.3174/ajnr.a6173
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Zero TE–MRA in the Characterization of Cerebrovascular Diseases: A Feasibility Study

Abstract: BACKGROUND AND PURPOSE: Zero TE-MRA is less sensitive to field heterogeneity, complex flow, and acquisition noise. This study aimed to prospectively validate the feasibility of zero TE-MRA for cerebrovascular diseases assessment, compared with TOF-MRA. MATERIALS AND METHODS: Seventy patients suspected of having cerebrovascular disorders were recruited. Sound levels were estimated for each MRA subjectively and objectively in different modes. MRA image quality was estimated by 2 neuroradiologists. The degree of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 27 publications
3
24
0
Order By: Relevance
“…Similar to previous reports (23,42), we also found that zTE-MRA resulted in lower quality imaging of distal small branched vessels than TOF-MRA (Figure 4). In essential, zTE-MRA is a continuous ASL-based angiography method (15).…”
Section: A B E C D Fsupporting
confidence: 91%
See 2 more Smart Citations
“…Similar to previous reports (23,42), we also found that zTE-MRA resulted in lower quality imaging of distal small branched vessels than TOF-MRA (Figure 4). In essential, zTE-MRA is a continuous ASL-based angiography method (15).…”
Section: A B E C D Fsupporting
confidence: 91%
“…With these advantages, zTE-MRA might be considered with added clinical value in diagnosis of ICAS. Notably, Shang et al (23) recently published an interesting study that also confirmed the clinical value of zTE-MRA for imaging cerebrovascular diseases. Compared with their study, we used DSA as the reference for ICAD diagnosis, which we believe is more accurate than the CTA applied in their investigation (40).…”
Section: A B E C D Fmentioning
confidence: 80%
See 1 more Smart Citation
“…A previously reported 5‐point scale was applied 29 : 0 = no noise, 1 = mild noise, 2 = moderate noise, 3 = loud noise, 4 = very loud noise, and 5 = unacceptable noise/cancellation of MR imaging. Objective measurements were described in previous study 16 . Briefly, a sound‐level meter (Type AS804; Smart Sensor, Guangdong, China) was used to measure the sound intensity under ambient and scanning conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Among the various ASL‐MRA approaches, zero‐echo‐time (ZTE) MRA can diminish the saturation effect, minimize magnetic susceptibility, and reduce acoustic noise by integrating a continuous ASL (cASL) strategy, ZTE acquisition, and three‐dimensional (3D) radial sampling trajectories 14 . Previous studies have demonstrated the promising superiority of cASL‐ZTE‐MRA over TOF‐MRA in the follow‐up assessment of coiled aneurysms and the diagnosis of intracranial artery diseases 15–20 . However, Holdsworth et al implied that marginal blurring along the vessel walls occurs in cASL‐ZTE‐MRA and might be mistaken for vascular lesions 21 .…”
mentioning
confidence: 99%